MediaThing – A Learning Scenario Targeting on Research Skills - Winkelnkemper, Felix; Keil, Reinhard (Proceedings of EdMedia: World Conference on Educational Media and Technology.)

studiolo communis - Seng, E.-M; Keil, Reinhard; Oevel, Gudrun

Unterstützung kontingenter Wissensarbeit. Ein Rahmenwerk für die Entwicklung digitaler Arbeitsumgebungen zur Unterstützung des Forschungsdiskurses in den Kulturwissenschaften - Keil, Reinhard

STUDIOLO. Kooperative Forschungsumgebungen in den eHumanities - Seng, E.-M; Keil, Reinhard; Oevel, Gudrun

Data science in schools from the perspective of contextual informatics - Selke, Harald

Challenges for Annotation Concepts in Music - Hadjakos, Aristotelis; Iffland, Joachim; Keil, Reinhard; Oberhoff, Andreas; Veit, Joachim (International Journal of Humanities and Arts Computing)

Learning {\ "o} natural infrastructures: A technology-centered approach to the development of new educational potentials - Keil, Reinhard (Education in the digital age - balance sheet and perspectives)

Design of virtual research environments for {\ "u} r detailed philological work - Keil, Reinhard ("Eh, the old man, I would like to pay attention". Festschrift for {\ "u} r Joachim Veit for his 60th birthday)

DeLFI 2015 - The 13th e-Learning Conference on Computer Science of the E-Learning Section of the Society for Computer Science eV - Pongratz, Hans; Keil, Reinhard

WebArena - R {\ "a} spacious structures for ü r the learning locations of the future - Winkelnkemper, Felix; Oberhoff, Andreas

20 years of learning with the World Wide Web - technology and education in dialogue

Learn with, through and {\ "about the WWW - Keil, Reinhard; Selke, Harald

Virtual knowledge {\ "a} ume - From the presentation of content to virtual learning ä tten - Keil, Reinhard; Selke, Harald

Development of a structured process of interaction design for {\ "u} r nat ü local user interfaces - Klompmaker, Florian

Empirical validation of design patterns - Schild, Christian; Petrausch, Vanessa (Human and Computer 2015 - Proceedings)
Patterns serve to codify design knowledge. By embedding them in a hypothesis-driven design, it is possible to develop them further into sample languages. For this it is necessary to resolve the underlying conflicts in the form of design hypotheses and to validate them empirically in order to enable further use and generalization. In this article, an experiment is presented that describes this procedure and demonstrates the interplay between theory formation and codification of design knowledge using two examples.

Virtual knowledge {\ "a} ume - From the presentation of content to virtual learning ä tten - Keil, Reinhard; Selke, Harald

Development of a structured process of interaction design for {\ "u} r nat ü local user interfaces - Klompmaker, Florian

Empirical validation of design patterns - Schild, Christian; Petrausch, Vanessa
Patterns serve to codify design knowledge. By embedding them in a hypothesis-driven design, it is possible to develop them further into sample languages. For this it is necessary to resolve the underlying conflicts in the form of design hypotheses and to validate them empirically in order to enable further use and generalization. In this article, an experiment is presented that describes this procedure and demonstrates the interplay between theory formation and codification of design knowledge using two examples.

Twenty years of learning with the World Wide Web - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix
n the summer of 1994, courses at universities were supported for the first time through the use of the World Wide Web. With the introduction of this new technology, high expectations quickly arose that the established forms of teaching and learning in schools and universities would be replaced and that the institutions themselves might even prove to be superfluous. Twenty years later, it turns out that there is a great gap between hope and reality. Some of the ideas at the time that, for example, having access to the world's knowledge at any time would make textbooks superfluous, turned out to be naive in retrospect. Characteristic of the ideas at that time was the assumption that didactic and organizational problems of teaching and learning could be solved purely technically.

Zwischen Design und Flexibilität - Zur Ergonomie des Flat Design - Winkelnkemper, Felix; Keil, Reinhard

Forschendes Lernen durch semantisches Positionieren - Jakoblew , Marcel; Keil, Reinhard; Winkelnkemper, Felix (Proceedings der HDI 2014)

Hypothesengeleitete Gestaltung von Benutzungsoberflächen - Keil, Reinhard; Schild, Christian

Knowledge integration processes and distributed knowledge organization - Keil, Reinhard

Twenty years of learning with the World Wide Web - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix

Zwischen Design und Flexibilität - Zur Ergonomie des Flat Design - Winkelnkemper, Felix; Keil, Reinhard

Approaches for an informational separation of powers in learning platforms - Keil, Reinhard; Winkelnkemper, Felix

„Do You Speak Usability?“ – Aktueller Stand des Glossars und des Curriculums für den „Certified Professional for Usability and User Experience (CPUX)“ der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter; Polkehn, Knut

Contextual tagging in the coactive knowledge organization - K {\ "u} hnel, Birger

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten

Computer science and education - A struggle for creative sovereignty in society? - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix (FIfF-Kommunikation)

Media contexts - context media - Keil, Reinhard

A Taxonomy-Based Approach Towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard

Computer science and society as a field of computer science - Engbring, Dieter; Selke, Harald
In this article we report on the experiences of a redesigned teaching in the field of computer science and society (IuG). The reasons for the redesign and the concept are outlined. We have condensed our experiences into theses: 1. Computer science and society should be a compulsory course in the bachelor's degree, in which students get an overview of which social framework conditions are relevant for them and how they can be incorporated into practice. 2. Historical contents of computer science are to be processed here by considering current developments in the context of their genesis.

User Centered Design of an Interactive Mobile Assistance and Supervision System for Rehabilitation Purposes - Klompmaker, Florian; Workowski, Anke; Thronicke, Wolfgang; Ostermair, Florian; Willemsen, Detlev; Hoffmann, D

Towards Multimodal 3D Tabletop Interaction using Sensor Equipped Mobile Devices - Klompmaker, Florian; Nebe, Karsten; Eschenlohr, Julien

The technical potential of digital boards - Selke, Harald; Winkelnkemper, Felix
This article explains the technical potential of digital boards with which more and more schools are being equipped. A consideration of current usage scenarios of these interactive whiteboards shows that a large part of this potential is still unused and the deficits of the software often have to be circumvented with tricks, especially for use in demanding, student-oriented lessons. Finally, the further development of existing teaching scenarios using this technical potential shows that considering the technical possibilities of digital boards can motivate new didactic scenarios.

Der Qualitätsstandard für Usability Engineering der German UPA - Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Geis, Thomas; Kluge, Oliver; Bogner, Christian; Polkehn, Knut

Base Requirements for Virtual Tabletop Groupware Artifacts - Tobias, Müller; Nebe, Karsten; Klompmaker, Florian

Collaborative work on interactive displays - design, operation and fields of application - Fischer, Holger Gerhard; Klompmaker, Florian (M & C, humans and computers)

Das Heinz Nixdorf Institut: Über 25 Jahre interdisziplinär erfolgreich - Keil, Reinhard

EVALUATION OF WHOLE-BODY NAVIGATION AND SELECTION TECHNIQUES IN IMMERSIVE 3D ENVIRONMENTS - Klompmaker, Florian; Dridger, Alexander; Nebe, Karsten (Proceedings of the ASME 2012 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)
Since 2010 when the Microsoft Kinect with its integrated depth-sensing camera appeared on the market, completely new kinds of interaction techniques have been integrated into console games. They don’t require any instrumentalization and no complicated calibration or time-consuming setup anymore. But even having these benefits, some drawbacks exist. Most games only enable the user to fulfill very simple gestures like waving, jumping or stooping, which is not the natural behavior of a user. In addition the depth-sensing technology lacks of haptic feedback. Of course we cannot solve the lack of haptic feedback, but we want to improve the whole-body interaction. Our goal is to develop 3D interaction techniques that give a maximum of freedom to the user and enable her to perform precise and immersive interactions. This work focuses on whole-body interaction in immersive virtual environments. We present 3D interaction techniques that provide the user with a maximum of freedom and enables her to operate precisely and immersive in virtual environments. Furthermore we present a user study, in which we analyzed how Navigation and Manipulation techniques can be performed by users’ body-interaction using a depth-sensing camera and a huge projection screen. Therefore three alternative approaches have been developed and tested: classical gamepad interaction, an indirect pointer-based interaction and a more direct whole- body interaction technique. We compared their effectiveness and preciseness. It turned out that users act faster, while using the gamepad, but generate significantly more errors at the same time. Using depth-sensing based whole-body interaction techniques it became apparent, that the interaction is much more immersive, natural and intuitive, even if slower. We will show the advantages of our approach and how it can be used in various domains, more effectively and efficiently for their users.

Integrating Usability Engineering in the Software Development Lifecycle Based on International Standards - Fischer, Holger Gerhard (Proceedings of the 4th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS), Copenhagen, Denmark)

Summary and Outlook - Keil, Reinhard; Metternich, Hans-J {\ "u} rgen; Ritzenhoff, Steffan

Durchl {\ "a} ssigkeitsorientierte Bildung - Keil, Reinhard; Niehus, Dominik; Ossenschmidt, Daniel

Automatic emotion recognition - technologies, interpretation and applications - Brand, Marcel; Klompmaker, Florian; Schleining, Peter; Weiss, Fabian (Computer science spectrum)

Passability in education - a challenge for ü r the future - Keil, Reinhard; Metternich, Hans-J {\ "u} rgen; Ritzenhoff, Steffan

Enriching Disaster Control Management based on Human-Centered Design - Fischer, Holger Gerhard; Klompmaker, Florian (Proceedings of the 9th International Conference on Information Systems for Crisis Response and Management (ISCRAM), Vancouver, Kanada)

German UPA Qualitätsstandard für Usability Engineering - Behrenbruch, Kay; Bogner, Christian; Fischer, Holger Gerhard; Geis, Thomas; Geitner, Claudia; Heimgärtner, Rüdiger; Hofmann, Britta; Hunkirchen, Peter; Kluge, Oliver; Litzenberg, Britta; Molich, Rolf; Polkehn, Knut; et al.

Learning scenarios for school 2.0 - Jakoblew, Marcel; Niehus, Dominik; Selke, Harald
In order to support everyday school life, the educational platform "Education in Dialogue" was developed and continuously improved over a period of more than ten years in an evolutionary process with user participation. The aim of this article is to show how sustainable support can be achieved by not focusing on the basic possibilities of network-based work, but using everyday practice as a starting point. In order to decide how the school assignment can be optimally supported in a specific embodiment, we develop »learning scenarios«. Based on a didactic approach, a technical concept and a usage guide are designed.

E-learning strategies: best practice or careful structural renewal? - Keil, Reinhard; Schild, Christian; Winkelnkemper, Felix

dSensingNI – A Framework for Advanced Tangible Interaction using a Depth Camera - Klompmaker, Florian; Nebe, Karsten; Fast, Alex
This work presents an approach to overcome the disadvantages of existing interaction frameworks and technologies for touch detection and object interaction. The robust and easy to use framework dSensingNI (Depth Sensing Natural Interaction) is described, which supports multitouch and tangible interaction with arbitrary objects. It uses images from a depth-sensing camera and provides tracking of users fingers of palm of hands and combines this with object interaction, such as grasping, grouping and stacking, which can be used for advanced interaction techniques.

Authenticated Tangible Interaction using RFID and Depth-Sensing Cameras - Supporting Collaboration on Interactive Tabletops - Klompmaker, Florian; Fischer, Holger Gerhard; Jung, Helge (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI), Valencia, Spanien)

Designing Multi-Modal Map-Based Interfaces for Disaster Management - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI), Valencia, Spanien)

Computer science and society - a lecture in the master's degree in computer science - Selke, Harald (FIfF communication)
There have been and still are lectures on the subject of computer science and society at some universities. Some of these are still held by those who can be considered the founders of this subject in Germany. In recent years, however, some of the protagonists from the very beginning have already retired and the positions have been filled or partially rededicated with successors of various origins. Aspects that were previously dealt with within this subject are now addressed in other subjects. For the "new" lecturers the question arises how the problem that Stefan Köpsell formulated very honestly can be addressed: "Since I have not yet known any satisfactory systematics for computer science and society, the lecture consists of a collection of widely spread, each separately understandable themed mosaic tiles. Everyone has to put their overall understanding of the topic together personally. ”(Köpsell, 2012) In this contribution, attempts to design a lecture Computer Science and Society within the given framework (previous lectures, content-related delimitation of other events, supplementary events, previous knowledge and Expectations of the students) and the experiences associated with the implementation are reported. As presumably every course, this represents work in progress. delimitation of the content of other events, supplementary events, previous knowledge and expectations of the students) and the experiences associated with the implementation are reported. As presumably every course, this represents work in progress. delimitation of the content of other events, supplementary events, previous knowledge and expectations of the students) and the experiences associated with the implementation are reported. As presumably every course, this represents work in progress.

Interdisciplinary {\ "a} t as a challenge for ü r e-learning research - Keil, Reinhard; Wessner, Martin (i -com magazine f {\ "u} r interactive and cooperative media)

Between innovation and suitability for everyday use - "Lernstatt Paderborn" - Keil, Reinhard (Paderborn University {\ "a} ts-Zeitschrift)

A coactive support approach for {\ "u} r processes of social reality construction in product creation processes - Holzwei {\ ss} ig, Kai

Multi-touch, tangible and pen-based interaction in incident planning - Nebe, Karsten; Fischer, Holger Gerhard; Klompmaker, Florian; Jung, Helge

Virtual Learning Spaces for Co-Active Learning - Keil, Reinhard; Selke, Harald (Proc. of Int. Conf. on Improving University Teaching)
Kollaboratives Lernen kann im Großen und Ganzen durch verteilte, unterbrochene kooperative Prozesse charakterisiert werden, da die Interaktion mit anderen Lernern und Lehrenden zu verschiedenen Zeiten an verschiedenen Orten stattfindet. Um die zeitlich und räumlich verteilten Lernaktivitäten zu integrieren, muss ein virtueller Lernraum bereitgestellt werden der einerseits als Arena kooperativer Interaktionen dient und andererseits gleichzeitig ein verteiltes externes Gedächtnis durch persistente Lernobjekte bietet. Das Konzept des ko-aktiven Lernens umfasst eine Vielzahl von technischen Konzepten und Funktionen, die kollaboratives Lernen in unterschiedlichsten Lernarrangements unterstützen.

Multi-Touch Interaction for Disaster Management.} - Paelke, Volker; Nebe, Karsten; Klompmaker, Florian; Jung, Helge

Hypothesis- guided technology design as the basis of contextual computer science - Keil, Reinhard

Smart Fiducials: Advanced Tangible Interaction Techniques through Dynamic Visual Paterns - Klompmaker, Florian; Nebe, Karsten; Jung, H

User Centered Design Process of OSAMI-D: Developing User Interfaces for a Remote Ergometer Training Application - Klompmaker, Florian; Nebe, Karsten; Busch, Clemens; Willemsen, Detlev (Proceedings of the International Conference on Health Informatics)

KoProV: A Learning Approach for Coordinated Learning of Modeling and Simulation Based on Knowledge Modules - Laroque, Christoph; Schulte, Jonas (Proceedings of the 2011 Spring Simulation Multiconference)

WasabiBeans - Web Application Services and Business Integration - Schulte, Jonas (Proceedings of the 13th International Conference on Enterprise Information Systems, SciTePress - Science and Technology Publications, Beijing, China)

Computer scientists, ergonomists and chemists are shaping the future. E-Portofolios support {\ "u} the flow rate in education and training - Rudolph, S; Niehus, Dominik

Koi School - Towards the Next Level of Communication, Organization and Integration in Education - Schulte, Jonas; Keil, Reinhard; Klaholt, D; Sauer, J (Proceedings of the 13th International Conference on Enterprise Information Systems, SciTePress - Science and Technology Publications, Beijing, China)

Support {\ "u} support of the co-active research discourse through synergies between e-learning and e-science - Schulte, Jonas; Keil, Reinhard; Oberhoff, Andreas

Laboratory 2.0 - Towards and Integrated Research Environment for Engineering Mechanics - Schulte, Jonas; Keil, Reinhard; Rybka, Johann; Ferber, Ferdinand (Proceedings of the 13th International Conference on Enterprise Information Systems, SciTePress - Science and Technology Publications, Bejing, China)

KoForum - Cooperative research environment for {\ "u} for cross-organizational scientific Laboratory work - Schulte, Jonas; Rybka, Johann; Ferber, Ferdinand; Keil, Reinhard

Semantic Positioning - Supporting Knowledge Work through Semantic Spatial Arrangements - Erren, Patrick

A Holistic Model for Integrating Usability Engineering and Software Engineering Enriched with Marketing Activities - Fischer, Holger Gerhard; Nebe, Karsten; Klompmaker, Florian

Authenticated entries on multi-touch tables - Jung, Helge; Nebe, Karsten; Klompmaker, Florian; Fischer, Holger Gerhard

Exploiting New Interaction Techniques for Disaster Control Management using Multitouch-, Tangible- and Pen-based-Interaction - Nebe, Karsten; Klompmaker, Florian; Jung, Helge; Fischer, Holger Gerhard

Der Qualit {\ "a} tsstandard f ü r Usability engineering of the German UPA: Current status of the work - Fischer, Holger Gerhard; Bogner, Christian; Geis, Thomas; Polkehn, Knut; Zimmermann, Dirk